Neurocognitive evaluation and intervention in boys and girls with behavioral symptoms (2021)
This book aims at exposing the effect of the implementation of an intervention program aimed at children with behavioral difficulties belonging to vulnerable social sectors in the city of Neiva. This document is based on the context of investigations conducted worldwide, in Latin American and nationally on evaluation and intervention programs focused on reducing behavioral deficits, which allow a better adaptation of children to different areas of their daily lives. Having in mind this, one of the most studied development in relation to behavioral difficulties is social cognition, mainly the domain of the Theory of Mind (ToM), which explains from the cognitive point of view, emotional and communicative deficiencies in social situations, problems that are evident in a population diagnosed with disorders associated with behavioral symptoms, such as conduct disorder and attention deficit hyperactivity disorder (adhd). The book begins by presenting the historical development and conceptualization of disorders; subsequently, family, clinical, adaptive characteristics are described; as well as the executive functioning and social cognition in children who take part in the intervention program, ending with the results and contributions of the study to the knowledge.